Economic Globalization and Inflation in China: A Multivariate Approach. (May 2015) - Zhang, Chengsi; Song, Ke; Wang, Fang
Abstract This paper evaluates whether globalization has increased the role of global factors in driving inflation in China. Unlike other published studies on the relationship between globalization and inflation, which mostly use Phillips curve models, this paper uses multivariate dynamic models to examine the dynamic interactions between globalization and inflation in China. Empirical results with quarterly data spanning from 1995 to 2012 show that the global output gap significantly affects the dynamics of inflation in China. In particular, the global output gap is superior to the domestic output gap in predicting domestic inflation. Impulse response and variance decomposition analyses reinforce this finding. Our results indicate that the central bank of China should take developments in global output into account in its monetary policy‐making process.